Socioeconomic determinants of anaemia in preschool children in Uttar Pradesh: evidence from NFHS-4 survey - Kumar, Anil; Gulati, Bal Kishan; Sahu, Damodar; Ranjan, Varsha; Rao, M. V. Vardhana (International Journal Of Community Medicine And Public Health, 2020)
Background: In India, 89 million preschool children (6-59 months) suffer from anaemia. As per NFHS-4, the prevalence of anaemia in Uttar Pradesh was 63.2%. A study was undertaken to estimate the prevalence of anaemia among preschool children and to examine rural-urban differentials and association of socioeconomic determinants with anaemia. The secondary data of the National Family Health Survey-4 conducted in the year 2015-16 was used. Methods: The prevalence of anaemia was calculated and chi-square test and binary logistic regression was carried out to identify the association between anaemia status and socioeconomic factors. Results: Results show that 78% and 77% children in 12-23 months age group were anaemic in urban and rural areas respectively. Around 72% and 65% children whose mothers had no formal education were anaemic in urban and rural areas respectively. Around 73% of children belonging to poorest wealth index in urban areas and 64% belonging to poorer wealth index in rural areas were anaemic. Around 70% children whose mothers had anaemia were anaemic in both urban and rural areas of the state. Conclusions: The association between anaemia in preschool children and different socioeconomic variables was profound. Educational status of mother and anaemia in mothers have a significant role in reduction of anaemia. The socioeconomic conditions of households, education level of mothers and their anaemia status need to be improved to reduce anaemia in preschool children in Uttar Pradesh and it requires immediate attention of planners and policy makers.